System of actions to enhance emotional intelligence in school athletes attennis of field (Original) (Revista científica Olimpia, 2019)
Emotional intelligence refers to a way of interacting with the world, which takes into account emotions and includes skills such as control of impulses, self-awareness, motivation, empathy, which helps overcome difficulties and are essential for social adjustment. In this definition, emotions are of paramount importance, and they play a decisive role in sports because they appear as a result of the athlete of the involvement in a social relationship given by the same sport activity performing having a function of behavior management. With this work we intend to establish a diagnosis of skills and abilities that encompasses emotional intelligence in athletes as well as the tasks that socializing agents must perform to enhance emotional intelligence so that it has a methodological, practical utility with social results that are reflected in competitive results. The research provides a system of psychological actions that allows the technical staff to develop emotional intelligence in the comprehensive training of Tennis of Field athletes, constituting an important work tool in the hands of coaches and sports technicians in search of better results in the competitive field of the athlete. For the development of this research, we athletes involment of the same sport Tennis of Field, School Category, ranging from 9-10 and 11-12 years and an average age of 11.6 years of the same female sex.
Keywords: emotional intelligence; system of actions; abilities; tennis of field; athletes